Mirror, Mirror: Adoption and Mothering in Film - Greenway, Kate (Journal of the Motherhood Initiative for Research and Community Involvement, 2017)
What narratives are being told about adoption, by whom and for whom, and what consequences do they have? How might my birthmother, adoptive mother or I have received and internalized messages about adoption and mothering transmitted via the pervasive medium of film Barbara Estrin notes in her review of Marianne Novy’s Reading Adoption how all of us are shaped, consciously or unconsciously by “the anxieties that cultural influences instill (217).” These anxieties, Novy suggests, must have shaped those women who have had to make difficult decisions regarding their desire, or lack of desire, to raise a child. Film, as one of the most pervasive and accessible cultural products, can serve as a mirror to the zeitgeist of the times in which it was produced, allowing viewers to think critically about the messages of such narratives and how, or whether, they have changed over time. Adoption and illegitimacy remain primarily a marginal plot device in film. Those films that do make these themes central may have influence on how those inside and outside the adoption triangle view themselves. I look at a selection of films created over a period of seventy years about unplanned pregnancy and adoption. I hope to measure the shift in cultural images of adoption and mothering in film, or lack thereof, to gauge whether the anxieties that Novy mentions have been exposed or whether gaps, omissions and misconstructions remain.